The Effect of Ribavirin on Reactive Astrogliosis in Experimental Autoimmune Encephalomyelitis - Irena Lavrnja; Danijela Savic; Ivana Bjelobaba; Sanja Dacic; Iva Bozic; Ana Parabucki; Nadezda Nedeljkovic; Sanja Pekovic; Ljubisav Rakic; Mirjana Stojiljkovic (Elsevier, 2012)
Experimental autoimmune encephalomyelitis (EAE) is an animal model of CNS inflammatory and demyelinating disease multiple sclerosis. Microglia and astrocytes represent two related cell types involved in the brain pathology in EAE. Accumulations of hypertrophic reactive astrocytes, intensely stained with glial fibrillary acidic protein (GFAP), which also expressed vimentin, are prominent features of EAE lesions. Recent studies from our laboratory reported that ribavirin attenuated the disease process in EAE by reducing clinical and histological manifestations. EAE was induced in genetically susceptible Dark Agouti rats with syngeneic spinal cord homogenate in complete Freund's adjuvant. Real time PCR and immunohistochemistry were used for determination of GFAP and vimentin gene and tissue expression. We have observed the increased gene and tissue expression of GFAP and vimentin in EAE rats. Ribavirin treatment significantly decreased the number of reactive astrocytes at the peak of disease. At the end of the disease, we have observed reactive GFAP+ and vimentin+ astrocytes in both immunized and ribavirin-treated groups, accompanied by increased level of GFAP mRNA. The present study indicates that ribavirin may have the ability to attenuate astrocyte proliferation and glial scaring at the peak of the disease and modulate the astroglial response to EAE during the time-course of the disease. Keywords:: experimental autoimmune encephalomyelitis (EAE), astrocyte, spinal cord, ribavirin